Why can't we be friends? A narrative review of the challenges of making and keeping friends for children and adolescents with Attention-Deficit/Hyperactivity Disorder - Neprily, Kirsten M.; Climie, Emma A.; McCrimmon, Adam; Makarenko, Erica (Frontiers in Developmental Psychology, 2025)
This narrative review explores the friendship characteristics of children and adolescents with Attention-Deficit/Hyperactivity Disorder (ADHD). Previous literature on ADHD has focused on attentional, academic, and behavioral challenges. Social impairment and peer relationships in children and adolescents with ADHD have been recognized as a critical area of research. Adolescents with ADHD frequently experience clinically significant and impairing social and friendship difficulties. Despite the immense research on factors that contribute to why children and adolescents with ADHD have difficulty making and keeping friends and why friendship is especially important for youth with ADHD, to date, it has not been synthesized in a way that is comprehensive to our understanding. In this review, friendship, friendship formation, the benefits of friendship, and the features of friendship (i.e., friendship quality and stability) will be discussed. Second, the magnitude of friendship challenges faced by children and adolescents with ADHD, as well as the impact these peer difficulties have on friendship quality and stability, will be presented. Next, the dominant conceptualization of why children and adolescents with ADHD struggle to make and keep friends, which focuses on factors such as ADHD symptomatology, executive functioning, social cognition, and emotion regulation, is reported. This review will conclude with suggestions for future research and interventions that may be beneficial for ameliorating friendship difficulties among children and adolescents with ADHD.